Dose‐response patterns in low and high intensity cognitive behavioral therapy for common mental health problems. Issue 3 (6th February 2020) - Robinson, Louisa; Kellett, Stephen; Delgadillo, Jaime
Abstract: Background: Cognitive‐behavioral therapy (CBT) is effective for the treatment of common mental health problems, but the number of sessions required to maximize improvement in routine care remains unclear. Aim: This study aimed to examine the dose‐response effect in low (LiCBT) and high (HiCBT) intensity CBT delivered in stepped care services. Methods: A multi‐service data set included N = 102 206 patients across N = 16 services. The study included patients with case‐level depression and/or anxiety symptoms who accessed LiCBT and/or HiCBT. Patients with posttreatment reliable and clinically significant improvement in standardized outcome measures (PHQ‐9, GAD‐7) were classified as treatment responders. Survival analyses assessed the number of sessions necessary to detect 50%, 75%, and 95% of treatment responders. The 50% and 95% percentiles were used to define the lower and upper boundaries of an adequate dose of therapy that could be used to inform the timing of treatment progress reviews. Analyses were then stratified by diagnosis, and cox regression was used to identify predictors of time‐to‐remission. Results: Most responders (95%) attained RCSI within 7 sessions of LiCBT and 14 sessions of HiCBT. Patients with social anxiety disorder, posttraumatic stress disorder, and obsessive‐compulsive disorder required HiCBT and lengthier treatments (6–16 sessions) to maximize improvement. Conclusions: Distinctive dose‐response patterns are evident for LiCBT and HiCBT, which can be used to support treatment planning and routine outcome monitoring.